PERFORMANCE OF INDICATORS USED IN THE REGULAR RISK ASSESSMENT FOR COVID-19 - S. Hong; B.I. Kim; J. Oh; M. Lee; H. Kim; S. Tak (International Journal of Infectious Diseases, 2023)
Intro: Since November 2021, gradual changes in non-pharmaceutical interventions (NPI) had begun in consideration of the socio-economic cost and the high rate of COVID-19 vaccination. As an effort to monitor the COVID-19 situation and the effect of NPIs, regular risk assessment for COVID-19 has been conducted based on the input from the external advisory committee. This paper examines the correlation between the risk assessment results and other indicators, such as the incidence of COVID-19, public perception, community mobility, and the government policy from November 2021 to May 2022. Methods: For weekly regular risk assessment of COVID-19, the data were collected from the National Infectious Disease Surveillance System website, which included incidence, mortality, and % of severe cases. Other indicators were from regular surveys on perceived risk among the public, community mobility from the Google website, and the government's response policy from The Oxford Stringency Index. The level of risk was classified into five levels from very low to very high. The level of COVID-19 risk and its correlation with the COVID-19 incidence, risk perception, community mobility, and government policy were examined. Findings: The result of the correlation analysis showed the highest positive correlation between the risk level and risk perception (r=0.86, CI 0.72-0.94). This indicates that the actual risk level and the risk perceived by the public are similar. Among the incidence-related indicators, the number of new severe cases of COVID-19 per week showed the highest correlation with the risk level (r=0.62, CI 0.33-0.80). Conclusion: The high correlation between the weekly severe cases and the overall COVID-19 risk level suggests that Korea's COVID-19 policy priority was mainly at protecting the high-risk population